Exercise prescription for the prevention and treatment of chronic diseases in primary care: Protocol of the RedExAP study. - Alicia Saz-Lara; José Alberto Martínez Hortelano; María Medrano; Raquel Luengo-González; Miriam Garrido Miguel; Montserrat García-Sastre; José Ignacio Recio-Rodriguez; Daniel Lozano-Cuesta; Iván Cavero-Redondo (PLoS ONE)
Background Existing evidence supports the effectiveness of exercise in preventing and treating chronic diseases, yet its integration into clinical practice remains limited. This study protocol aims to address the evidence-practice gap by exploring barriers to exercise prescription in primary care and developing a clinical practice guideline (CPG). Methods Employing a qualitative approach, focus groups will be conducted to investigate primary care professionals' challenges in prescribing exercise and patients' adherence to recommendations. Phenomenological analysis will facilitate data interpretation. Data triangulation, expert analysis, and quality criteria will ensure study reliability. The CPG development process is outlined, emphasizing transdisciplinary collaboration and patient involvement. Conclusion The RedExAP study responds to the imperative for evidence-based exercise integration in primary care. The study's combined qualitative exploration and CPG development present the potential to improve health outcomes and cost-effectiveness. By elucidating primary care professionals' and patients' perspectives, the study contributes to enhancing exercise prescription adoption. The innovative transdisciplinary approach aligns with the 2030 Agenda, promoting better population health and greater social well-being, showing promise in alleviating chronic disease burdens. This study's findings lay the groundwork for advancing evidence-based exercise interventions within primary care to transform chronic disease management.